2021
DOI: 10.3892/mco.2021.2231
|View full text |Cite
|
Sign up to set email alerts
|

Primary vulvar leiomyosarcoma localized in the Bartholin's gland area: A case report and review

Abstract: Vulvar sarcomas located in the Bartholin's gland area are extremely uncommon mesenchymal vulvar tumors. These neoplasms can be mistaken as Bartholin' gland benign lesions such as cysts or abscesses, leading to a delay in the diagnosis of underlying malignancy. Currently, only a few cases of these aggressive cancers have been reported in the literature. A 42-year-old female patient without any previous complaint presented to Obstetrics and Gynecology Department of 'G. Chaztikosta' General Hospital due to a vulv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…This case is the first case of vulvar leiomyosarcoma showing a rapid increase in size during pregnancy reported in the Gulf region. The literature review revealed few documented cases of leiomyosarcoma located in the female genital tract [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This case is the first case of vulvar leiomyosarcoma showing a rapid increase in size during pregnancy reported in the Gulf region. The literature review revealed few documented cases of leiomyosarcoma located in the female genital tract [1][2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Women often have difficulty articulating vulvar symptoms to medical practitioners, therefore, all women with vulvar symptoms should be examined. It arises most frequently from the labia majora, followed by, in decreasing order, the Bartholin's gland area, clitoris, and labia minora with clinical similarities between them leading to difficulties in clinical diagnosis [2,4,5,7,9,10]. The mean age of incidence has been reported to be between 33 and 40 years, with a range between 15 and 84 years [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations